Nursing Students' Attitudes Toward Nursing Education Research and Participation in Pedagogical Research - Burrell, Sherry A; Ross, Jennifer Gunberg; Heverly, Mary Ann; Menginie, Tina M (Nurse educator, 2020)
Nursing students overall have positive attitudes toward research, but no studies have explored students' attitudes toward education research or pedagogical research participation. The purposes of this study were to explore nursing students' attitudes toward research in general, education research, and participation as subjects in pedagogical research; describe the relationships among these attitudes; and identify associated factors. A mixed-methods, descriptive, cross-sectional study design was used. Nursing students' (N = 195) attitudes about research in general, education research, and participation in pedagogical research were predominantly positive and directly correlated. Age was significantly associated with attitudes about education research and research participation, whereas program year was associated only with research participation. The most prevalent barrier to research participation was time. Findings provide valuable insight about nursing students' attitudes toward research that may be used to design protocols to enhance student participation in pedagogical research.